Innovative skills to increase cohesion and communication in couples - Laser-Maira, Julie Anne; Nicotera, Nicole (Oxford University Press, 2019)
Couples therapy is not always successful or enjoyable for either the client or the therapist. Innovative Skills to Increase Cohesion and Communication in Couples discusses evidence-based clinical techniques and skills that support and nurture couples in their relationship. Each chapter begins with a succinct overview of a technique, evidence that supports it, and ideas for assessment to ensure that it is appropriate for the couple. Subsequent sections of each chapter provide clear examples of approaches so that new or seasoned clinicians will have the requisite knowledge for effective implemen.
Keywords: Couples therapy.; Couples Therapy; Thérapie de couple.; HEALTH & FITNESS -- Diseases -- General.; MEDICAL -- Clinical Medicine.; MEDICAL -- Diseases.; MEDICAL -- Evidence-Based Medicine.; MEDICAL -- Internal Medicine.; Couples therapy; Electronic books.